Recent environmental change and atmospheric contamination on Svalbard as recorded in lake sediments – an introduction - Birks, Harry John Betteley; Jones, Vivienne J.; Rose, Neil L. (Springer, 2004)
This is the first in a series of nine papers published in this special issue dedicated to recent environmental change on Svalbard. H.J.B. Birks, Vivienne J. Jones, and Neil L. Rose were guest editors of this special issue. This paper outlines an interdisciplinary project on recent environmental change and atmospheric contamination on the high Arctic archipelago of Svalbard (76º30'N – 80º30'N). It describes the rationale and aims of the project and summarises the location, climate, geology, vegetation, and land-use of Svalbard.